BELAJAR SEBAGAI SUATU PROSES AKTIVITAS KOGNITIF - Ismail, Wahyuni (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2007)
Learning is a word often heard and it is an activity done by everyone started since birth, childhood, teens, up to the adulthood. It can be stated that learning is a process occurring from birth to death. It is an activity done a long the life. Furthermore, Learning is a process occurring in various aspects. How can the learning process occurring according to human cognitive activity? According to psychology, learning process is formed due the presence of the psychological ability of the internal aspect of human to respond the stimulus. The response is then processed through indra. From indra, perception, association, reproduction, fantasy, memory, thinking, are all formed to rich what is called intellectual ability. Cognitive activity process is different between one individual to another.